The Möbius-Wall congruences for p-adic L-functions of CM elliptic curves - Bouganis, Thanasis (Mathematical proceedings of the Cambridge Philosophical Society, 2014)
In this paper we prove, under a technical assumption, the so-called “Möbius-Wall” congruences between abelian p-adic L-functions of CM elliptic curves. These congruences are the analogue of those shown by Ritter and Weiss for the Tate motive, and offer strong evidences in favor of the existence of non-abelian p-adic L-functions for CM elliptic curves.
First published online 11 November 2013
Gesehen am 30.09.2020